"So what if I am Laz?" - Serdar, Ayşe (Poligrafi, 2021)
This study argues that the ethnic Laz in Turkey resort to irony, humor and mockery to cope with and negotiate the stereotypes, ethnic humor and mockery they encounter in their interactions with outsiders. The trope of irony, humor and mockery have enabled the Laz to navigate the national and regional hierarchies and reproduce their symbolic boundaries regardless of the common and ardent appropriation of Turkishness. In so doing, the Laz can more subtly challenge the official ideology of uniformity. While the public use of Lazuri is still considered a threat to the negotiated boundaries of Lazness, new instruments present creative displays of their ethnic capital which do not contradict present day principles of Turkish nationalism, and offer a legitimate sharing of intimacy without embar-rassment. The Laz, like other non-Turkish Muslim peoples of the Black Sea region, abandoned their politically threatening ethnic distinctions, appropriated the capital of Turkishness through their performances, and coped with mockery and stigma by ironizing differences and negotiating, trivializing or selectively appropriating the stereotypes imposed upon them. Ironically, they have “out-performed” ethnic Turks in certain ways, in their search for acceptance as Turks, achieving upward mobility and avoiding forms of stigmatization.
Keywords: ethnic identity; ethnicity; Etnična pripadnost; Humor; Ironija; irony; Laz; Lazijci; mockery; Narodnosti (manjšine); Posmeh; Turkey